BUCCAL PENETRATION ENHANCERS-AN OVERVIEW - DODLA, SUMANJALI; VELMURUGAN, SELLAPPAN (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Over the last decade, there has been a particular interest in delivering drugs in buccal mucosa and aiming to increase bioavailability of varied controlled drug delivery systems (CDDS), mucoadhesion (the capability of a object to adhere to mucous membranes) occupies a unique position. Buccal administration of API provides a convenient route of administration for both systemic and local actions. It provides direct entry into the systemic circulation thus avoiding the hepatic first-pass effect and degradation in the gastrointestinal tract. However permeability of oral mucosa is limiting factor which relatively low compared to intestinal mucosa and the skin. When permeability differences between various organs of the oral region are taken into consideration, buccal membrane found to be more permeable. In order to deliver wider classes of drugs across the buccal mucosa, the barrier potential of mucosa must be reduced. This requisite has forced the study of buccal penetration enhancers that will overcome the permeability barrier of the buccal mucosa. Numerous compounds have been evaluated for penetration enhancing activity, including bile salts, surfactants, fatty acids and derivatives, ethanol, cyclodextrins and chitosan etc. The purpose of this review is to identify the structural and chemical nature of the permeability barrier the buccal mucosa, to clarify the mechanisms of action of buccal penetration enhancers.